A avaliação no ensino de espanhol: crença-ação de duas professoras da escola pública - Avila, Andriza Pujol de (2018)
The evaluation of school learning is crucial to the course of teaching and learning. With the new outlines of linguistic education there is no space for an evaluation of learning oriented exclusively to the objectivity and homogeneity, the new processes require to consider aspects of subjectivity and the use of diversified tools that stimulate the collaboration and the interaction among the learners. In the teaching of foreign languages it is necessary the teaching, as well as the evaluation, to be ruled by the same approach (SCARAMUCCI, 1997); otherwise, the process will occur in disharmony. These orientations are also part of the legal regulations that rule the Brazilian teaching of Foreign Language and must be presented to the teachers throughout their initial formation; however, not always this happens. The theme evaluation of learning, many times, is neglected in the Language courses (PELISSON, 2007; ZOCARATTO, 2010), for that reason, many teachers do not have the adequate knowledge to give a true dimension of the role of the school evaluation. In this research, we investigated which is the relation between the belief and action about the evaluation of learning in the practice of two teachers of Spanish, foreign language of the public school. For this, it was described the contexts of the two schools and performed the observation of the classes, afterwards, gathered and analyzed the belief of the two teachers and established the relation belief-action with emphasis for the contextual influences. It is a study case of qualitative approach and with basis in the contextual approach proposed by Barcelos (2001). The results indicate that the actions of the teacher Julia both referring to the teaching and learning and the evaluation of learning, seem permeated by a hybridism that catches her to a more traditional posture, without trying to advance towards the Sociocultural Approach, with few contextual interferences in her practice, since that they seem minimized by her belief and regulations of education. The teacher Celine presents some proposals of learning with communicative potential, however, many others of strongly grammatical bias. The evaluation of learning performed by her presents strong formative tendency and the context affects directly her actions. Finally, we confirmed the thesis of the research that the belief of the teacher directly or indirectly influences his/her actions.